Was Molière a Feminist? The Case of Célimène, an Independent Woman - Koloini, Diana (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2022)
Molière has often been treated as an anti-feminist, but this qualification disregards the complexity of his woman figures. In The Misanthrope, Célimène represents an exceptional woman figure that is a novelty in the classical literature. A master of brilliant conversation, she is a witty and charming salon lady. Her freedom causes concerns particularly for Alceste, the protagonist who dominates the play with his critical worldview. His assessment of Célimène’s conformism, coupled with her fickleness and falsity, was echoed by the majority of traditional commentaries that deemed her to be a slanderous coquette, hence a relatively banal figure. Countering such simplifications, the paper tries to establish Célimène as a complex, rich and subtle figure and explores the question to what extent she displays an independent spirit which equals Alceste’s. It examines the possibilities of woman’s freedom within the patriarchal framework of the time, and beyond.